GRP78 protects a disintegrin and metalloprotease 17 against protein‐disulfide isomerase A6 catalyzed inactivation. Issue 21 (11th October 2017) - Schäfer, Miriam; Granato, Daniela C.; Krossa, Sebastian; Bartels, Anne‐Kathrin; Yokoo, Sami; Düsterhöft, Stefan; Koudelka, Tomas; Scheidig, Axel J.; Tholey, Andreas; Paes Leme, Adriana F.; Grötzinger, Joachim; Lorenzen, Inken
Abstract : The shedding of ectodomains is a crucial mechanism in many physiological and pathological events. A disintegrin and metalloprotease‐17 (ADAM17) is a key sheddase involved in essential processes, such as development, regeneration, and immune defense. ADAM17 exists in two conformations which differ in their disulfide connection in the membrane‐proximal domain (MPD). Protein‐disulfide isomerases (PDIs) on the cell surface convert the open MPD into a rigid closed form, which corresponds to inactive ADAM17. ADAM17 is expressed in its open activatable form in the endoplasmic reticulum (ER) and consequently must be protected against ER‐resident PDI activity. Here, we show that the chaperone 78‐kDa glucose‐regulated protein (GRP78) protects the MPD against PDI‐dependent disulfide‐bond isomerization by binding to this domain and, thereby, preventing ADAM17 inhibition. Abstract :